Al-Siraj Al-Wahhaj Fi Qissat Al-Isra Wa Al-Mi’raj by Imam Shihab Al-Din Al-Qalyubi (D. 1069 AH) Study and Editing, From Page [53/B] To [54/A] - al-rawi , Noor Thair Abd Jaber Hassan; karim, Qaia jalil (Journal of Ecohumanism, 2024)
This research aims to study the book "Al-Siraj Al-Wahhaj fi Qissat Al-Isra wa Al-Mi’raj" by its author Abu Al-Abbas Shahab Al-Din Al-Qalyubi. The study includes content from page [53/b] to [54/a], which outlines the third ascension represented by the meeting of our Prophet Muhammad (peace be upon him) with Joseph the Just, the eleventh son of Jacob. He is described as having beauty and grace, being one of the most renowned figures in the Quran and the Torah. The author also mentioned occasions of his meeting in the third heaven, corresponding to events in the third year of Hijra, including: the conspiracy of his brothers against him and his being thrown into the well, which parallels the Quraysh’s conspiracy to kill the Messenger and throw him into a pit. I relied on the methodology of scholars specialized in this field for the investigation, and may Allah grant us success in presenting it in a satisfactory and acceptable manner.